STATE OF SOIL RESEARCH IN SOUTHWESTERN NIGERIA: THE ACHIEVEMENTS, CHALLENGES AND WAY FORWARD - OJETADE, J. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2024)
Soil is the bedrock for food, fibre, fuel, raw materials, foundation for most engineering constructions, sink for industrial pollution, determinant of land quality and habitat to millions of micro-organisms useful in medicine, biodegradation and recycling of wastes.  In spite of its huge life-support services, it has not been given adequate attention, thus resulting in the dearth and uncoordinated information about soils in Nigeria, leading to abuse and misuse of soil resources. To reposition soil research in transforming agriculture in Nigeria, regional assessment of the state of soil research in different geopolitical zones of the country becomes desirable. The objectives of this paper were to review the state of soil research in southwestern Nigeria, identify the salient achievements so far recorded, emphasize the challenges militating against sustainable soil research efforts in southwestern Nigeria and suggest possible ways forward.